Numerical Analysis Related to the ROCOM Pressurized Thermal Shock Benchmark - Thomas Höhne; Sören Kliem (Fluids, 2022)
The development, verification, and validation of Computational Fluid Dynamics (CFD) codes in reference to nuclear power plant (NPP) safety has been a focus of many research organizations over the last few decades. Therefore, a collection of Rossendorf Coolant Mixing Test Facility (ROCOM) CFD-grade experiments was made obtainable to line up a global International Atomic Energy Agency (IAEA) benchmark regarding Pressurized Thermal Shock (PTS) situations. The benchmark experiment describes the complicated flow structures in mixed convection zones of the RPV during PTS events. The experiments were utilized to validate CFD codes. Additionally, an experiment with no buoyancy forces was elite to point out the influence of density variations. Compared to earlier studies, the turbulence models of the CFD code improved a lot. The turbulence modeling approach shows a respectable agreement with the experimental data.